Analisis Pemikiran Al-Ghazali dan Ibnu Miskawaih Tentang Pendidikan Anak - Suci Rachmawati (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2025)
This study examines the comparison of Al-Ghazali and Ibn Miskawaih's thoughts on the concept of children's education and its relevance in the context of contemporary Islamic education. The phenomenon of moral degradation among the younger generation and the tendency of the modern education system to emphasize the cognitive aspect more than the moral and spiritual aspects are the background for the urgency of this research. The purpose of the research is to analyze the concept of children's education according to the two figures, identify the similarities and differences in their thinking, and examine their relevance to the context of contemporary Islamic education. This study uses a narrative-based descriptive qualitative method based on literature study by exploring the primary works of the two figures, namely